Catalytic Oxidation of Methane: Pd and Beyond - Monai, Matteo; Montini, Tiziano; Gorte, Raymond J.; Fornasiero, Paolo (European journal of inorganic chemistry, 2018)
This brief review is focused on recent advancements in methane catalytic oxidation, an important reaction for environmental remediation and clean power generation. Particular attention is given to Pd‐based catalysts and novel strategies to gain a fundamental understanding of the reaction mechanism and to improve the catalytic activity and stability of Pd catalysts. The power of combined approaches exploiting nanostructured catalysts, operando spectroscopic and microscopic measurements and computational methods is demonstrated. Methane is a widely available and low‐carbon resource, but its emissions are a serious environmental concern. Catalytic oxidation is a mature technology to convert methane to less climate forcing CO2. Here, we discuss the recent advances in the field, focusing on thermal stability and poisoning resistance of catalytic materials.